PEMBINAAN BACA TULIS AL-QUR’AN DI TPA NURUL HAQ PO’RIGA DESA TONGKONAN BASSE - M. Sultan S; Rifal Ramadhan; Ira Mahirah; Nur Mala Syam (IAI DDI Mangkoso, 2025)
The Al-Qur'an is a guide that was revealed to all mankind, meaning that the Al-Qur'an must have been taught to humans from an early age starting from reading and writing. There are several main bases for understanding the Qur'an, namely the introduction ofhijaiyah letters, tajwid, and the meanings contained. In Po’riga, In Enrekang there is an informal institution called TPA Nurul Haq Po’riga which teaches children to read and write the Al-Qur’an. The problem faced there was the lack of coaches who managed the children during the process, as a result the coaches were a little overwhelmed in dealing with the relatively large number of children. In addition, the level of Al-Qur'an literacy and children's understanding of tajwid is still lacking. The specificobjective of this coaching is to be able to apply the knowledge that is known and gain additional knowledge during the process at TPA Nurul Haq Po’riga. The general purpose of this assistance is to assist Nurul Haq Po’riga TPA supervisors in teaching children. In this mentoring, the author uses the mentoring method to the supervisor during the teaching and learning process. The result of this training is that children begin to be orderly in the teaching and learning process and are able to recite verses of the Qur'an properly.